Pengujian Sistem Steering Gear Pada Saat Sea Trial Kapal Perintis Sabuk Nusantara 750 DWT - Adi Kurniawan Yusim; Iwan; Bambang Sri Waluyo (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
In the sea trial, many things were tested, one of which was the steering gear test. This test aims to determine the time it takes the ship to turn at a certain angle according to the provisions of the Biro Klasifikasi Indonesia (BKI) and check the function of the steering system. On the Sabuk Nusantara 750 DWT Pioneer Ship carried out two types of tests, namely the main steering gear and the auxiliary steering test. The main steering gear test is carried out in a series of tests with a joystick on the steering gear panel on the ship's bridge. Auxiliary steering test is divided into two types, namely using the steering wheel and solenoid which is located in the engine room. Testing the steering gear on this archipelago belt pioneer ship meets the requirements of BKI.